Synergistic Effect of Pyrvinium Pamoate and Azoles Against Aspergillus fumigatus in vitro and in vivo - Sun, Yi; Gao, Lujuan; Zhang, Youwen; Yang, Ji; Zeng, Tongxiang (Frontiers in Microbiology, 2020)
The effects of pyrvinium pamoate alone and in combination with azoles (itraconazole, posaconazole and voriconazole) were evaluated against Aspergillus fumigatus both in vitro and in vivo. A total of 18 clinical strains of A. fumigatus were studied, including azole-resistant isolates harboring the combination of punctual mutation and a tandem repeat sequence in the Cyp51A gene (AFR1 with TR34/L98H and AFR2 with TR46/Y121F/T289A). The in vitro results revealed that pyrvinium individually exhibited MIC of 2 μg/ml against AFR1 but was ineffective against other tested strains (MIC >32 μg/ml). Nevertheless, synergistic effect of pyrvinium with itraconazole, voriconazole, or posaconazole were observed in 15 (83.3%, FICI 0.125-0.375), 11 (61.1%, FICI 0.258-0.281), and 16 (88.9%, FICI 0.039-0.281) strains, respectively, demonstrating the potential of pyrvinium in reversion of itraconazole and posaconazole resistance of both AFR1(FICI 0.275, 0.281) and AFR2 (FICI 0.125, 0.039). The effective MIC ranges in synergistic combinations were 0.25-8 μg/ml for pyrvinium, 0.125-4 μg/ml for itraconazole, 0.125 μg/ml for both voriconazole and posaconazole, demonstrating 4 to 32-fold reduction in MICs of azoles and up to 64-fold reduction in MICs of pyrvinium, respectively. There was no antagonism. The effect of pyrvinium-azole combinations in vivo were evaluated by survival assay and fungal burden determination in Galleria mellonella model infected with AF293, AFR1 and AFR2. Pyrvinium alone significantly prolonged the survival of larvae infected with AF293 (P<0.01) and AFR1 (P<0.0001), and significantly decreased tissue fungal burden of larvae infected with AFR1(P<0.0001). Pyrvinium combined with azoles significantly improved larvae survival (P<0.0001) and decreased larvae tissue fungal burden in all three isolates (P<0.0001). Notably, despite AFR2 infection was resistant to voriconazole or pyrvinium alone, pyrvinium combined with voriconazole significantly prolonged survival of both AFR1 and AFR2 infected larvae (P<0.0001). In summary, the preliminary results indicated that the combination with pyrvinium and azoles had the potential to overcome azole resistance issues of A. fumigatus and could be a promising option for anti-Aspergillus treatment.